Polymer production by Klebsiella pneumoniae 4-hydroxyphenylacetic acid hydroxylase genes cloned in Escherichia coli. - Gibello, A (1995)
The expression of Klebsiella pneumoniae hpaA and hpaH genes, which code for 4-hydroxyphenylacetic acid hydroxylase in Escherichia coli K-12 derivative strains, is associated with the production of a dark brown pigment in the cultures. This pigment has been identified as a polymer which shows several of the characteristics reported for microbial melanins and results from the oxidative activity of 4-hydroxyphenylacetic acid hydroxylase on some dihydroxylated compounds to form o-quinones. A dibenzoquinone is formed from the oxidation of different mono- or dihydroxylated aromatic compounds by the enzyme prior to polymerization. We report a hydroxylase activity, other than tyrosinase, that is associated with the synthesis of a bacterial melanin.